Implementasi Algoritma Naïve Bayes Untuk Menentukan Calon Penerima Beasiswa Di SMK YPM 14 Sumobito Jombang - Wahyu ningsih; Budiman Budiman; Izzatul Umami (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
Scholarships are grants in the form of financial assistance given to individuals that aim to be used for the continuation of the education achieved. With this scholarship program, it is hoped that it can help students who have problems in financing. The selection of scholarship recipients at SMK YPM 14 Sumobito still experiences problems in decision making, because the assessment process is not always decided based on definite considerations but the policy of the decision makers who ultimately determine the scholarship recipients. This is because there is no method that can predict prospective scholarship recipients. Eligibility of prospective scholarship recipients is determined by applying the Naïve Bayes method. This method was chosen because it was able to study the previous case data used as test data. After testing with the Naïve Bayes algorithm using the Rapidmaner tool, the results were 90.48% accuracy, 96.88% precision, 83.33% recall each. So that it can be said as a good key to apply for prospective scholarship recipients. Keywords: (scholarship assistance, Data Mining, Naïve Bayes).